Tinjauan Terhadap Landasan Hukum dan Dasar Pertimbangan Hakim Dalam Memberikan Rehabilitasi Terhadap Anak Pelaku Tindak Pidana Narkotika (Studi Putusan Nomor 988/Pid.B/2011/PN.Jkt.Pst) - F, Fitriani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Law Number 35 of 2009 does not provide exceptions for child offenders, but for the verdict handed down by the judge regarding what punishment is imposed and the severity of the punishment imposed, it must be considered from the social situation regarding the facts of the child offender. Before the judge makes a verdict against a child who commits a criminal act, there are several things that are the basis for consideration for the judge. The judge's decision will affect the child's life in the future, therefore the judge must be sure that the decision to be taken is the most appropriate and also fair This research uses a legislative approach and a case approach in its normative juridical research methodology. The results of this study show that the legal basis for the provision of rehabilitation for children of narcotics offenders is in accordance with the provisions of Law Number 35 of 2009, and Law Number 11 of 2012, in Decision Number 988/Pid.B/2011/PN.Jkt.Pst, the judge determined to provide rehabilitation to children who commit narcotics crimes on the basis that children should be protected from the impact of narcotics crimes by making improvements to the child's mentality and behavior by being entrusted to a rehabilitation home Narcotics with the intention that after completing the rehabilitation period from the rehabilitation center, the child can improve himself, return to the original situation, return to his parents and society and realize that narcotics crimes are very dangerous for him and others.